Medication-related osteonecrosis of the jaw. Issue 4 (April 2020) - Patel, Kishan; Walshaw, Emma; Aranha, Charolene
Medication-related osteonecrosis of the jaw (MRONJ) is a rare, but well-documented, complication following the administration of anti-resorptive and anti-angiogenic drugs. MRONJ has a negative effect on quality of life, and can result in reduced social contact, pain and masticatory difficulties. Prescription of implicated medication is within the remit of GPs, and thus National Institute for Health and Care Excellence (NICE) guidelines have been published to inform prescribing. Careful consideration of the potential deleterious oral side-effects of these drugs is needed. NICE guidelines on the prescribing of bisphosphonates for osteoporosis acknowledge that osteonecrosis of the jaw was not included in the adverse events when the economic model was assessed. This article provides an overview of MRONJ, highlighting key areas for possible GP intervention when caring for patients at risk of developing MRONJ, and what to do if MRONJ is suspected.